Comparison of Indonesian and Japanese New-Vocabularies in the Context of the Covid-19 Pandemic: Morphosemantic Study - Br. Barus, Murniati; Pujiono, Mhd. (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Situational and social contexts influence language to change. Various online discourses during the current pandemic have given rise to new COVID-19 vocabulary in Indonesian and Japanese. Therefore, this study will examine and compare Indonesian and Japanese new vocabulary during the COVID-19 pandemic. This study used a morphosemantic theory in descriptive qualitative research. The data is a collection of new COVID-19 vocabulary from March 2020 to December 2021 from Indonesian and Japanese online newspapers. Listening and recording are used to collect data, and interactive model analysis is used to analyse it. Data collection found 24 new Indonesian words and 30 Japanese words. The two languages' vocabularies have 21 similar meanings. One Japanese word has no Indonesian equivalent. New Indonesian vocabularies form from adopted acronyms and loanwords. In Japanese, vocabulary comes from loanwords, native words, kango, and combinations. The new words regarding the COVID-19 outbreak are owned by both Indonesian and Japanese, but their comparison is not necessarily the same even though the context is the same. Both countries define or handle COVID-19 differently. Forming words from both languages affects the form of new vocabulary. According to the findings of this study, a global situation such as a pandemic affects various developments in vocabulary formation in Indonesian and Japanese. This study helps foreign language learners and researchers, especially Japanese, understand new newspaper vocabulary. It fills gaps left by previous research, which focused on single-language data and context. An analysis of COVID-19 vocabulary words in Indonesian and Japanese.